A specific A/T polymorphism in Western tyrosine phosphorylation B-motifs regulates Helicobacter pylori CagA epithelial cell interactions - Zhang, Xue-Song; Tegtmeyer, Nicole; Traube, Leah; Jindal, Shawn; Perez-Perez, Guillermo; Sticht, Heinrich; Backert, Steffen; Blaser, Martin J. (PLoS Pathogens, 2015)
Helicobacter pylori persistently colonizes the human stomach, with mixed roles in human health. The CagA protein, a key host-interaction factor, is translocated by a type IV secretion system into host epithelial cells, where its EPIYA tyrosine phosphorylation motifs (TPMs) are recognized by host cell kinases, leading to multiple host cell signaling cascades. The CagA TPMs have been described as type A, B, C or D, each with a specific conserved amino acid sequence surrounding EPIYA. Database searching revealed strong non-random distribution of the B-motifs (including EPIYA and EPIYT) in Western H. pylori isolates. In silico analysis of Western H. pylori CagA sequences provided evidence that the EPIYT B-TPMs are significantly less associated with gastric cancer than the EPIYA B-TPMs. By generating and using a phosphorylated CagA B-TPM-specific antibody, we demonstrated the phosphorylated state of the CagA B-TPM EPIYT during H. pylori co-culture with host cells. We also showed that within host cells, CagA interaction with phosphoinositol 3-kinase (PI3-kinase) was B-TPM tyrosine-phosphorylation-dependent, and the recombinant CagA with EPIYT B-TPM had higher affinity to PI3-kinase and enhanced induction of AKT than the isogenic CagA with EPIYA B-TPM. Structural modeling of the CagA B-TPM motif bound to PI3-kinase indicated that the threonine residue at the pY+1 position forms a side-chain hydrogen bond to N-417 of PI3-kinase, which cannot be formed by alanine. During co-culture with AGS cells, an H. pylori strain with a CagA EPIYT B-TPM had significantly attenuated induction of interleukin-8 and hummingbird phenotype, compared to the isogenic strain with B-TPM EPIYA. These results suggest that the A/T polymorphisms could regulate CagA activity through interfering with host signaling pathways related to carcinogenesis, thus influencing cancer risk.
EVALuna2:26288